ANALISIS LAPORAN KEUANGAN PEMERINTAH PUSAT (LKPP) TAHUN ANGGARAN 2007 - Budiartha, I Ketut (INPUT Jurnal Ekonomi dan Sosial, 2009)
With the end of year budget 2007, the government has succeeded to arrange the Report of Government Budget(LKPP). The report consists of the Report of Budget Realization, the Report of Cash flow, and the GovernmentBalance Sheet. These reports have been audited by Indonesian Supreme Audit Agency and it has been rewarded anopinion of “denying to give opinion (disclaimer)”. The same opinion has been given by the institution since 2004.By publishing the reports, then the society will be able to judge the ability of government in managing the previousperiod of budget and also to predict for the future budget. The technique to analyze the LKPP is general financialanalysis which is used to evaluate the management of private sector such as (1) comparative financial statementanalysis, (2) common-size financial statement analysis, (3) ratios analysis, (4) cash flow analysis, and (5) valuation.According to comparative analysis there is a surplus budget of last year development and it is positive from273.914.695,00 rupiah into minus 7.387.288.768 rupiah. For the wealth of country 1.600.211.672.865.020,00rupiah and actually it is expensed from the debt 1.430.965.464.059.560.00, and the rest is taken from the countryfund 169.246.208.805.469,00The biggest contribution of the country income is taken from taxes for 69,37% and the rest for 30,39% is non-taxesincome. The country income is, then, used as government finance for 67%, being transfer to local government for33% and for the fund of particular autonomy and its adjustment for 4%.Based on financial ratio analysis, the actual current ratio for 2007 is 112%, meanwhile in the year of 2006 is117%. There is a reduction for 5%. For the debt ratio to modal in the year 2007 is 845%, it means every 1 rupiahof personal modal will be responsible for the debt of 845 rupiah. This condition shows the quantity of governmentasset 1.600.211.672.865.020,00 rupiah and it is taken 84,5% from the debt.